PERJUANGAN MULTIKULTURALISME PERHIMPUNAN INDONESIA TIONGHOA DALAM PERSPEKTIF REKOGNISI AXEL HONNETH - Rustono Farady Marta (Bricolage : Jurnal Magister Ilmu Komunikasi, 2018)
ABSTRACTSocial equality among human beings is the ideal condition that has been initiated by philosophers such as Hegel and Mead, but Axel Honneth offers a different perspective on both implementation levels and a more holistic perspective. One of the thoughts related to the acquisition of Honneth's recognition through his postulate, has illustrated that there is a struggle on the basis of awareness of respect and recognition of cultural identity in the realm of multiculturalism. In the struggle there are several steps that must be passed to obtain mutual recognition of the particular identity, where the working principle starts from the affective level of love, then the cognitive is in the realm of the legal order, until the intellectual intuition is poured in the form of solidarity. These three become forms of reciprocal relationships that lead to the acquisition of recognition in several stages in every phase of society's development. This is in line with the struggle of the Chinese Association of China (INTI) which is always at the forefront of diffusing the implementation of multiculturalism to the wider community. Recognition of the equal rights and obligations of citizens is an essential human role, as well as the ethnic Chinese Indonesian community that has become an integral and fundamental part of the Unitary State of the Republic of Indonesia (NKRI). Unfortunately, past political policies 'scratch' history track record that actually creates a negative perception related to the existence of this ethnic.Keywords: Axel Honneth Recognition, Multiculturalism, Perhimpunan INTIABSTRAKPemikiran Rekognisi Axel Honneth melalui postulasinya bahwa terdapat perjuangan pemerolehan rekognisi (the struggle for recognition), dimana prinsip kerjanya lebih didasarkan atas: cinta (love), tatanan hukum (legal order), dan solidaritas (solidarity). Hal ini sejalan dengan perjuangan Perhimpunan Indonesia Tionghoa (INTI) yang senantiasa berada di garis terdepan mendifusikan implementasi dari multikulturalisme pada masyarakat luas. Pengakuan akan kesetaraan hak dan kewajiban warga negara merupakan sesuatu peranan manusia yang sifatnya hakiki, demikian pula masyarakat etnis Tionghoa Indonesia yang telah menjadi bagian integral serta fundamental dari Negara Kesatuan Republik Indonesia (NKRI). Sayangnya kebijakan politik masa lampau ‘menggoreskan’ rekam jejak sejarah yang justru menimbulkan persepsi negatif terkait keberadaan etnis ini.Kata kunci: Rekognisi Axel Honneth, Multikulturalisme, Perhimpunan INTI